COMPARING THE EFFECTIVENESS AND EFFICIENCY OF USING ACCOUNTING APPLICATIONS (SWOT ANALYSIS) - Rustam, Akie Rusaktiva; Widiastutik, Rika Nur (Arthavidya Jurnal Ilmiah Ekonomi, 2024)
This study aims to compared the effectiveness and efficiency of using Accurate, Jurnal, and Zahir applications in improving company performance. The study used a qualitative approach with a descriptive method. Data were collected through in-depth interviews with four informants from various companies that have used the application, and supplemented with passive observation. The results of the study indicate that the use of accounting applications can improve operational effectiveness and efficiency through automation of accounting processes, reducing manual errors, and accelerating the creation of financial reports. Each application has specific advantages, such as the Cost and Profit Center feature in Accurate which allows analysis per department, and data integration between departments in Jurnal. However, some weaknesses were also found, such as the limited features in Zahir which have not been integrated with the e-commerce platform. Overall, the use of accounting applications has been shown to improve the effectiveness and efficiency in managing company finances, with the selection of the most appropriate application depending on the specific needs and technological capabilities of each company.